Virus susceptibility and resistance of Hungarian pepper varieties - Horváth, J.; Kazinczi, G.; Takács, A.; Pribék, D.; Bese, G.; Gáborjányi, R.; S., Kadlicskó (International Journal of Horticultural Science, 2000)
The aim of our study was to examine susceptibility or resistance of 18 pepper varieties to four viruses [tobacco mosaictobamovirus (TMV), sowbane mosaic sobemovirus (SoMV), NTN strain of potato Y potyvirus  (PVYNTN) and cucumber mosaic cucumovirus (CMV). Out of the 18 varieties, 13 were resistant to CMV infection. Thirteen varieties were susceptible to TMV, while five ones (Dabora Fl, Brill Fl, Feherozon Synthetic, Ciklon Fl, Cecil Fl) showed only local hypersensitive reaction. All of the tested pepper varieties showed resistance to SoMV. Eight varieties (Tuba, Fehérözön Synthetic, Boni, Alba Regia, Korona, Édesalma, Cecil Fl, Star) were found to be resistant to PVYNTN. Out of the examined varieties five (Boni, Alba Regia, Korona, Édesalma, Star) were resistant to three viruses (SoMV, CMV and PVYNTN). Only one (Cecil F1) displayed complex, extreme resistance to SoMV, PVYNTN, CMV and hypersensitive reaction to TMV, therefore this hybrid is very important in pepper breeding and growing for virus resistance.